2020
DOI: 10.1039/c9tb02523e
|View full text |Cite
|
Sign up to set email alerts
|

An injectable thermosensitive hydrogel loaded with an ancient natural drug colchicine for myocardial repair after infarction

Abstract: The intramyocardial injection of colchicine-loaded hydrogel system effectively promoted myocardial repair after infarction while minimizing the systemic toxicity of colchicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…Moreover, in clinical practice, colchicine has side effects, which limit its clinical use. In order to overcome the side effects of colchicine, Chen et al developed an intramyocardial delivery system of colchicine using an injectable, thermosensitive poly(lactide-co-glycolide)-poly(ethyleneglycol)poly(lactide-co-glycolide) polymer hydrogel as a vehicle for the treatment of MI while minimizing its systemic toxicity [12]. The data showed that colchicine, especially colchicine-containing nanoparticles, markedly attenuated the cardiac in ammation by inhibiting the generations of in ammatory cytokines after MI, and the colchicine-containing nanoparticles had great potential as an anti-in ammatory therapy for the treat of MI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in clinical practice, colchicine has side effects, which limit its clinical use. In order to overcome the side effects of colchicine, Chen et al developed an intramyocardial delivery system of colchicine using an injectable, thermosensitive poly(lactide-co-glycolide)-poly(ethyleneglycol)poly(lactide-co-glycolide) polymer hydrogel as a vehicle for the treatment of MI while minimizing its systemic toxicity [12]. The data showed that colchicine, especially colchicine-containing nanoparticles, markedly attenuated the cardiac in ammation by inhibiting the generations of in ammatory cytokines after MI, and the colchicine-containing nanoparticles had great potential as an anti-in ammatory therapy for the treat of MI.…”
Section: Discussionmentioning
confidence: 99%
“…PEG, LA, GA, and Sn(Oct) 2 were purchased from Sigma-Aldrich (St. Louis, MO, USA). As reported in a previous study [ 43 ], the PLGA–PEG–PLGA copolymer was synthesized by ring-opening polymerization approach. Poly(ethylene glycol) (PEG) (1500 g/mol, 60 g) was dried under vacuum in a three-necked flask as the macroinitiator.…”
Section: Methodsmentioning
confidence: 99%
“…As reported in a previous study [43], the PLGA-PEG-PLGA copolymer was synthesized by ring-opening polymerization approach. Poly(ethylene glycol) (PEG) was dried under vacuum in a three-necked ask as the macroinitiator.…”
Section: Preparation and Characterization Of Plga-peg-plga Thermogelmentioning
confidence: 99%